2021
DOI: 10.3389/fpsyg.2021.647740
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Are School Counseling Services Ready? Students' Psychological Symptoms, School Counselors' Views, and Solutions

Abstract: The purpose of the current study was to investigate the effects of COVID-19 on high school students' psychological symptoms and to understand how ready counselors and school counseling services are based on the data we have. Therefore, this research is designed under two different studies: (A) Study 1: Effects of COVID-19 pandemic on students' psychological symptoms and (B) Study 2: Views and expectations of students and school counselors about school counseling services. The first study was a quantitative stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 60 publications
3
44
0
1
Order By: Relevance
“…The impact of gender on anxiety (albeit with only a very small effect size) mirrors the findings by Alemany-Arrebola et al (2020) among college students, where women had higher scores in trait and state anxiety; the latter accentuated in cases where a relative had died -thus showing that the stressful situation of the pandemic and remote learning together with a critical event such as the illness and death of a relative or friend due to COVID-19 increases anxiety levels (and-in the case of the original studyinfluences the perception of academic self-efficacy). A similar conclusion was reported in Turkey by Aslan et al (2020), where female (as well as less physically active) students displayed higher levels of perceived stress and by Karaman et al (2021), in Switzerland by Amendola et al (2021), and in the US (Business Wire, 2021;Clabaugh et al, 2021), while among teachers a similar trend was observed in the Basque Country (Ozamiz-Etxebarria et al, 2021). In the general population, three studies carried out in Italy (Mazza et al, 2020;Moccia et al, 2020) and Iran (Moghanibashi-Mansourieh, 2020) showed women's mental health to be more impacted than men's; on the other hand, research in China (Cao et al, 2020;Chen et al, 2020;Huang and Zhao, 2021) and a meta-analysis by Cénat et al (2021a) of papers again mainly hailing from this country found no gender differences in females' and males' experience of pandemic-related stressors.…”
Section: Discussionsupporting
confidence: 70%
“…The impact of gender on anxiety (albeit with only a very small effect size) mirrors the findings by Alemany-Arrebola et al (2020) among college students, where women had higher scores in trait and state anxiety; the latter accentuated in cases where a relative had died -thus showing that the stressful situation of the pandemic and remote learning together with a critical event such as the illness and death of a relative or friend due to COVID-19 increases anxiety levels (and-in the case of the original studyinfluences the perception of academic self-efficacy). A similar conclusion was reported in Turkey by Aslan et al (2020), where female (as well as less physically active) students displayed higher levels of perceived stress and by Karaman et al (2021), in Switzerland by Amendola et al (2021), and in the US (Business Wire, 2021;Clabaugh et al, 2021), while among teachers a similar trend was observed in the Basque Country (Ozamiz-Etxebarria et al, 2021). In the general population, three studies carried out in Italy (Mazza et al, 2020;Moccia et al, 2020) and Iran (Moghanibashi-Mansourieh, 2020) showed women's mental health to be more impacted than men's; on the other hand, research in China (Cao et al, 2020;Chen et al, 2020;Huang and Zhao, 2021) and a meta-analysis by Cénat et al (2021a) of papers again mainly hailing from this country found no gender differences in females' and males' experience of pandemic-related stressors.…”
Section: Discussionsupporting
confidence: 70%
“…Given the variety of the students’ demographic background, school counselors should avail themselves of the optimal interventions to empower students. At this point, technique such as dialectical behavior therapy (DDT) which involves more mindfulness self-regulation or emotion regulation may be more suitable for adolescents (Karaman et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence revealed that students reportedly experienced more psychological distress during this pandemic period 14 , therefore the role of school Guidance and Counselling teachers is vital to provide detailed information on the risk factors, warning signs, coping skills, debunk the myths of suicide, and promote better help-seeking behaviours in both students and parents. iii.…”
Section: What Progressive Measures Should Be Considered?mentioning
confidence: 99%